Original paperAntinuclear antibodies in rosacea patients - Woźniacka, Anna; Salamon, Małgorzata; McCauliffe, Daniel; Sysa-Jędrzejowska, Anna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
Introduction : Rosacea is a common inflammatory disorder, characterized by a spectrum of facial manifestations. The clinical similarity to other dermatoses, like lupus erythematosus, might lead to misdiagnosis, particularly in patients with elevated antinuclear antibody titers. Aim : To assess the frequency, titer and specificity of antinuclear antibodies in rosacea patients and correlate these findings with clinical features. Material and methods : The study included 101 rosacea patients and 26 sex- and age-matched controls. Immunofluorescence antinuclear antibody testing was performed on HEp-2 substrates. Patients’ sera with ANA titers of 1 : 160 or higher were evaluated by Euroline analysis. Results : Over a half (53.5%) of rosacea patients had an ANA titer greater than or equal to 1 : 160. Within this group 13.86% had a titer of 1 : 320, 8.91% had a titer of 1 : 640, and 6.93% had a titer of 1 : 1,280 or higher. The specificity of these antibodies could not be identified. Elevated ANA titers were present more often in women (55.8%) than in men (44.15%). Only two of 26 healthy volunteers had elevated ANA titers. One had a titer of 1 : 160 and the other of 1 : 320. During a two-year observation period, after the initial ANA testing, none of the patients with ANA titers above 1 : 640 developed an apparent autoimmune disorder. Conclusions : Elevated ANA titers are commonly found in rosacea patients, what with simultaneously existing facial erythema and photosensitivity might lead to misdiagnosis of lupus erythematosus. Clinicians should beware of these findings to avoid misdiagnosing lupus erythematosus in rosacea patients with elevated ANA titers.